2010
DOI: 10.1097/ajp.0b013e3181dc7adc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Web-based Training About Opioid Therapy for Chronic Pain

Abstract: Exposure to an interactive web-based training focused on shared decision-making and communication skills was more effective than exposure to compatible practice guidelines for knowledge and self-reported competence in the management of chronic noncancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…A combined intervention that includes information materials, decision-making support and patient education units would probably be perceived as more effective for improving patient-centeredness. Other studies in the medical setting have shown combined interventions to be effective in enhancing patient-centered care [46–48]. Moreover, it is very likely that different patient populations were asked to participate during the two data collection periods.…”
Section: Discussionmentioning
confidence: 99%
“…A combined intervention that includes information materials, decision-making support and patient education units would probably be perceived as more effective for improving patient-centeredness. Other studies in the medical setting have shown combined interventions to be effective in enhancing patient-centered care [46–48]. Moreover, it is very likely that different patient populations were asked to participate during the two data collection periods.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when denying a patient's request for opioid therapy, it might prove beneficial to explicitly share one's reasoning when it pertains to concerns about their well‐being and safety. Although not in the context of evaluating chronic pain patient outcomes, randomized controlled trials of diverse communication interventions have indeed demonstrated positive effects on patient and provider communication outcomes , as well as on PCP self‐reported competence, satisfaction, and patient centeredness .…”
Section: Resultsmentioning
confidence: 99%
“…Sullivan et al 16 included depictions of clinical interactions in an interactive, Web-based training module regarding opioid therapy. Exposure to the training module, which also included standard summaries of evidence, increased physician knowledge and self-reported competence in the management of chronic noncancer pain.…”
Section: Discussionmentioning
confidence: 99%